Manajemen Strategi Pojok Baca dalam Menumbuhkan Minat Membaca Anak-Anak di Desa Sepit Kecamatan Keruak: Management Strategy for Reading Corners in Growing Children's Interest in Reading in Sepit Village, Keruak District - Ahmad Izzudin; Umar Bakri; Diah Ayu Puspita Sari; Nur Asiah Jamil; Randa Gusti Pradana (Al-Gafari : Manajemen dan Pendidikan, 2026)
Reading is the key to gaining quick access to information. However, researchers are concerned that many children still lack an interest in reading, especially children in Sepit village. In response to this problem, researchers have created an activity in the form of a reading corner strategy to foster children's interest in reading in Sepit village. The purpose of this activity is to explain and utilize the management of the reading corner in Sepit village. The method used in this study is a qualitative descriptive approach. The subjects of this study were the children of Sepit village. Data collection techniques used were observation, interviews, and documentation. The results of the activity indicate that effective management of the Sepit village reading corner, including the selection of appropriate and interactive books, as well as the involvement of the community and village government in supporting the reading corner activities, has a positive impact on children's reading interest. The implication of this study is the important role of the reading corner in increasing children's interest in reading in Sepit village.